# Given \cos(a)+\cos(b)=1, prove that 1−s^2−t^2−3s^2t^2=0, where s=\tan(\frac{a}{2}) and t=\tan(\frac{b}{2})

hadejada7x 2022-01-15 Answered
Given $\mathrm{cos}\left(a\right)+\mathrm{cos}\left(b\right)=1$, prove that $1-{s}^{2}-{t}^{2}-3{s}^{2}{t}^{2}=0$, where $s=\mathrm{tan}\left(\frac{a}{2}\right)$ and $t=\mathrm{tan}\left(\frac{b}{2}\right)$
You can still ask an expert for help

## Want to know more about Trigonometry?

Expert Community at Your Service

• Live experts 24/7
• Questions are typically answered in as fast as 30 minutes
• Personalized clear answers

Solve your problem for the price of one coffee

• Available 24/7
• Math expert for every subject
• Pay only if we can solve it

## Answers (3)

Elaine Verrett
Answered 2022-01-16 Author has 41 answers
Alternatively:
$\mathrm{cos}a=2{\mathrm{cos}}^{2}\frac{a}{2}-1$
${\mathrm{cos}}^{2}\frac{a}{2}=\frac{1}{1+{\mathrm{tan}}^{2}\frac{a}{2}}=\frac{1}{1+{s}^{2}}$
$\mathrm{cos}a+\mathrm{cos}b=2{\mathrm{cos}}^{2}\frac{a}{2}+2{\mathrm{cos}}^{2}\frac{b}{2}-2=$
$\frac{2}{1+{s}^{2}}+\frac{2}{1+{t}^{2}}-2=1$
###### Not exactly what you’re looking for?
RizerMix
Answered 2022-01-20 Author has 438 answers
$\frac{1-{t}^{2}}{1+{t}^{2}}+\frac{1-{s}^{2}}{1+{s}^{2}}=1$ $1+{s}^{2}-{t}^{2}-{s}^{2}{t}^{2}+1+{t}^{2}-{s}^{2}-{s}^{2}{t}^{2}=1+{s}^{2}+{t}^{2}+{s}^{2}{t}^{2}$ $⇒1-{s}^{2}-{t}^{2}-3{s}^{2}{t}^{2}=0$
###### Not exactly what you’re looking for?
alenahelenash
Answered 2022-01-24 Author has 343 answers
Hint: $\frac{1-{s}^{2}}{1+{s}^{2}}+\frac{1-{t}^{2}}{1+{t}^{2}}=1$ $⇔\frac{1-{s}^{2}}{1+{s}^{2}}=1-\frac{1-{t}^{2}}{1+{t}^{2}}$ $⇔\left(1-{s}^{2}\right)\left(1+{t}^{2}\right)=2{t}^{2}\left(1+{s}^{2}\right)$
###### Not exactly what you’re looking for?

Expert Community at Your Service

• Live experts 24/7
• Questions are typically answered in as fast as 30 minutes
• Personalized clear answers

Solve your problem for the price of one coffee

• Available 24/7
• Math expert for every subject
• Pay only if we can solve it